Extending semi-numeric reionization models to the first stars and galaxies. Issue 3 (23rd November 2017) - Koh, Daegene; Wise, John H
Abstract: Semi-numeric methods have made it possible to efficiently model the epoch of reionization (EoR). While most implementations involve a reduction to a simple three-parameter model, we introduce a new mass-dependent ionizing efficiency parameter that folds in physical parameters that are constrained by the latest numerical simulations. This new parametrization enables the effective modelling of a broad range of host halo masses containing ionizing sources, extending from the smallest Population III host haloes with M  ∼ 10 6  M⊙, which are often ignored, to the rarest cosmic peaks with M  ∼ 10 12  M⊙ during EoR. We compare the resulting ionizing histories with a typical three-parameter model and also compare with the latest constraints from the Planck mission. Our model results in an optical depth due to Thomson scattering, τe = 0.057, that is consistent with Planck . The largest difference in our model is shown in the resulting bubble size distributions that peak at lower characteristic sizes and are broadened. We also consider the uncertainties of the various physical parameters, and comparing the resulting ionizing histories broadly disfavours a small contribution from galaxies. The smallest haloes cease a meaningful contribution to the ionizing photon budget after z  = 10, implying that they play a role in determining the start of EoR and little else.